Comparison of the effectiveness of static stretching and hold relax technique on hamstring flexibility - A Randomized Control trial - Ayesha Nazir, Uzma Naz, Ayesha Ilyas, Syeda Fatima Murtaza, Sania Maqbool, Bayyaniha Zaheer, Muhammad Nouman Tabassum, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: In order to manage discomfort and increase range of motion, this study compared the effectiveness of static stretching versus the hold-relax approach on hamstring flexibility. Study design: The study design was Randomized Controlled Trial (RCT). Place & duration: This study was conducted in Physiotherapy Department and Rehabilitation center at Mayo Hospital Lahore.The duration of study was 4 months after approval of synopsis. Methodology: In ‘group A’ Static stretching is applied while in ‘group B’ Hold Relax technique of PNF was applied, while in ‘group C’ conventional physiotherapy was applied. Allocation of patients in two groups had done by computerized generated list. All groups will also receive conventional therapy, which will remain same throughout the study. The conventional therapy will include: Heating pad for 15 minutes, Hamstring isometric exercises, Ankle pumps exercise, Hamstring self-stretches [toe touching while standing or long sitting].Group A will receive static stretching for hamstring muscles while group B will receive PNF hold relax technique, group C will be benefited by the conventional physiotherapy. Treatment frequency will be 3 times a week. The duration of treatment will be 2 weeks in both groups. Results: Pair 1 had shown that the pre and post treatment comparison of Numeric pain rating scale mean score of pair 1 of group A before treatment was 7.5±1.083 which improved to 5.5±1.56. Pre and post treatment comparison of pair 2 of group B had showed that mean score before treatment was 7.6± 1.23 which was improved to 2.2±1.48. Pair 3 of group C improved from 8.3±0.778 to 4.8±1.02. Conclusion: The findings of this study led to the conclusion that static stretching is superior to the hold-relax strategy for treating hamstring stiffness. It lessens pain and enhances muscle function and flexibility. Keywords: Hold relax technique, hamstrings flexibility, static stretching